Chemical composition, secondary and primary metabolites of Tithonia diversifolia related to climate - Herrera, R.S.; Verdecia, D.M.; Ramírez, J.L. (Cuban Journal of Agricultural Science, 2020)
To establish the relationship between chemical composition, secondary metabolites, primary metabolites and digestibility of organic matter, dry matter, protein, NDF and ADF of Tithonia diversifolia and climatic factors, the correlation study was carried out. The indicators were: A) chemical composition: ADF, NDF, lignin, cellulose, hemicellulose, cellular content, OM, ash, N, Si, Ca, P and Mg; B) secondary metabolites: total tannins, total phenols, total condensed tannins, fiber-bound condensed tannins, free condensed tannins, alkaloids, saponins, triterpenes, steroids and flavonoids, and C) primary metabolites: glucose, fructose, sucrose, N, verbascose, stachyose and raffinose. Correlation coefficients (r) between climatic factors and chemical composition were variable and the highest values were obtained for cellulose, total rainfall and number of days with rain (-0.69 and -0.73, respectively). For secondary metabolites, total condensed tannins and free condensed tannins stood out with temperatures and indicators of rain (values of r between 0.62 and 0.85) and for the primary metabolites, verbascose and stachyose were better with temperatures (r higher than 0.78). In vitro digestibility of DM correlated (r between -0.63 and -0.91) with temperatures, rainfall and their distribution. Similar performance was registered for digestibility of organic matter and the r varied between -0.69 and -0.90. Digestibilities of CP, ADF and NDF only correlated with rainfall and their distribution (r between -0.74 and -0.87). Data showed the specific and variable effect of climate elements in the studied indicators, which is useful for the efficient management of this plant under climate change conditions. It is recommended to consider these results to counteract the negative effect that secondary metabolites of Tithonia diversifolia can cause in ruminant feeding systems, apply mathematical modeling to predict the performance of these substances with climatic factors and other aspects of this plant management, as well as extend this type of research to other plants of interest to livestock.